2000
DOI: 10.1034/j.1399-3038.2000.00065.x
|View full text |Cite
|
Sign up to set email alerts
|

Connections among parent and child atopic illnesses

Abstract: This study investigated parent-child connections for the atopic illnesses of asthma, eczema, food allergies, and hay fever, in a sample of 325 families. Parents reported whether they or their children currently had each condition and rated the frequency and intensity of its episodes; these ratings were combined to estimate illness severity. The data revealed five main findings. First, chi-square parent-child concordance analyses indicated that children of parents with any of the atopic illnesses studied were s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
16
1

Year Published

2002
2002
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 35 publications
(53 reference statements)
5
16
1
Order By: Relevance
“…Similarly, strong associations between allergy and asthma have been seen in other studies (13,14). Our study also supports previous studies (5,(15)(16)(17)(18)(19) showing that having at least one parent with asthma increases a child's risk of developing asthma. Whereas other studies report inconsistent associations between early respiratory illnesses and asthma, our findings of an association were consistent between communities.…”
Section: Discussionsupporting
confidence: 81%
“…Similarly, strong associations between allergy and asthma have been seen in other studies (13,14). Our study also supports previous studies (5,(15)(16)(17)(18)(19) showing that having at least one parent with asthma increases a child's risk of developing asthma. Whereas other studies report inconsistent associations between early respiratory illnesses and asthma, our findings of an association were consistent between communities.…”
Section: Discussionsupporting
confidence: 81%
“…14,15 The causes of atopy are not fully known to date, but high levels of concordance among parents and children are present in asthma, as well as in allergic rhinitis and atopic dermatitis. 36 Tobacco use in the group of 13-to 14-year old children was associated with current asthma. Tobacco exposure also has been reported as an important risk factor for development of asthma and allergic sensitization.…”
Section: Discussionmentioning
confidence: 98%
“…Several studies have indicated that maternal atopy and AD, even more profoundly than paternal AD, increases the risk of atopy and AD in the infant (5)(6)(7)(8). In a recent study, in comparison to paternal atopy, maternal atopy involved a more than 3-fold risk of atopy in child (8).…”
Section: Discussionmentioning
confidence: 99%
“…Although the evidence is inconclusive, breast-feeding during the first months after birth seems to protect the infant against AD, including atopic eczema (1), allergic rhinitis (2), asthma (3), and food allergy (4). However, it has been documented that parental and particularly maternal AD increases the risk of AD in the infant (5)(6)(7)(8). The intensive relationship between the mother and the infant during pregnancy and breast-feeding may result in modulation of the immune system of the infant to favor the development of allergic immune responder phenotype.…”
mentioning
confidence: 99%